2022
DOI: 10.3390/jpm12010109
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Solution in Personalized Computer-Aided Arthroscopy of Shoulder Prostheses

Abstract: Background: Early recognition of prostheses before reoperation can reduce perioperative morbidity and mortality. Because of the intricacy of the shoulder biomechanics, accurate classification of implant models before surgery is fundamental for planning the correct medical procedure and setting apparatus for personalized medicine. Expert surgeons usually use X-ray images of prostheses to set the patient-specific apparatus. However, this subjective method is time-consuming and prone to errors. Method: As an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The standard method usually used in the absence of implant documentation, i.e., the comparison of radiographs of the patient with radiographs of the shoulder prosthesis by a specialist, is time consuming and error prone. The results of the IMFC-Net model they developed were promising—an average accuracy of 89.09%, a precision rate of 89.54%, a recall rate of 86.57%, and an F1 score of 87.94% [ 23 ]. However, our model demonstrated the ability to detect shoulder endoprostheses with an accuracy of 98.80%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard method usually used in the absence of implant documentation, i.e., the comparison of radiographs of the patient with radiographs of the shoulder prosthesis by a specialist, is time consuming and error prone. The results of the IMFC-Net model they developed were promising—an average accuracy of 89.09%, a precision rate of 89.54%, a recall rate of 86.57%, and an F1 score of 87.94% [ 23 ]. However, our model demonstrated the ability to detect shoulder endoprostheses with an accuracy of 98.80%.…”
Section: Discussionmentioning
confidence: 99%
“…However, AI does not only support diagnostic processes; it can also help when planning and carrying out therapy. Sultan et al proposed three different deep learning-based frameworks to identify different types of shoulder implants in X-ray scans, mainly an ensemble network called the Inception Mobile Fully Connected Convolutional Network (IMFC-Net) [ 23 ]. Only selected examples are listed here, but they illustrate how broadly AI-based algorithms can be used.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies state the reason for this being the wide range over which an anteroposterior shoulder X-ray can be spread 53 . However, many recent studies have reported on ML algorithms that demonstrated accuracy over 90% 53,54,58 . Geng et al conducted a promising proof of concept showing a 93% accuracy and a 0.1 second average identification time 59 .…”
Section: Implant Identificationmentioning
confidence: 99%